Extending the Progressive Tradition to Poor Countries: The Role of Universities and Colleges - Shiko Gathuo (Laureate Education Inc, 2016)
American universities and colleges have always been a bastion of liberalism and progressive thought. Historically, the academic community has supported social justice issues, given a voice to the poor, minorities and the disadvantaged, and brought to light subjects that are considered taboo elsewhere. Indeed, many social movements have either started in American universities or been energized by the actions of university students and faculty, and often with the support of university administrations. Yet, when it comes to dealing with global issues that affect poor nations, universities have not always acted as change agents. In some cases, universities have to been passive onlookers or been complacent in participating in maintaining the status quo. This essay discusses the external environmental challenges and the internal constraints that universities and colleges must grapple with in their efforts to play in the global sphere. Further, it espouses ways in which universities might contribute to the global common good through their actions externally, particularly with regard to public policy, and internally within their campuses. A particular emphasis is given to Africa.